Unveiling direct and indirect impacts of the Three Gorges Project for supporting synergistic water-power management. (1st March 2022) - Han, Dengcheng; Huang, Gordon; Liu, Lirong; Zhai, Mengyu; Fu, Yupeng; Gao, Sichen; Li, Jianyong; Pan, Xiaojie
Abstract: Large-scale hydraulic projects (LHPs) have played an essential role in the development of the surrounding area. due to their multiple functions in both water and power systems. Various industries can benefit from LHPs through the supply chains differentially. However, systematic analysis to investigate such impacts at a sectoral level is lacking and the mechanism that how these LHPs can affect different sectors is still unknown. Herein a factorial top-down impact assessment model (FTIAM) is developed to evaluate the direct and indirect impacts of the Three Gorges Project (TGP) on the Yangtze River Economic Belt (YREB) from the perspective of water and power supplies at a sectoral level, and screen the factors and their interactions affecting such impacts. The vital final demand and consumption sectors inducing the most water and power-use produced by the TGP (WTGP, ETGP), as well as the related distribution patterns at different production layers will be identified. Key supply chain paths for water and power flows will also be traced to reveal how the TGP affects the whole socio-economic system step by step. Some findings are revealed: 1) Final demand is dominant to control the distribution patterns of WTGP and ETGP. 2) The distribution patterns of WTGP would change from U to L shape as final demand increases. 3) The final demand of Hubei province induces most WTGP while the area outside the YREB consumes most ETGP respectively. 4) Manufacture of foods and tobacco, and Construction are two key sectors that have a high reliance on WTGP and ETGP indirectly. For the conservation of the resources, policies within the YREB focusing on water-use efficiency of agriculture and manufacturing sectors, and power-use efficiency of sector CON and TI are essential. The enormous final demand for WTGP and ETGP in Jiangsu, Zhejiang, Hubei, Sichuan province calls for immediate actions to promote a more water-saving and energy-saving lifestyle. For the economic benefits, small or medium-size hydraulic projects might be the mainstream for the YREB in the following decades. Such results are conductive to support the synergistic management of water and energy resources within the YREB and provide a reference for promoting regionally sustainable development assisted by LHPs. Graphical abstract: Image 1 Highlights: The impacts of the Three Gorge Project alongside the supply chains are studied. Water and power flow from the Three Gorge Project are studied. Final demand dominates distribution patterns related to the Three Gorge Project. Food industry highly relies on water flow from the Three Gorge Project indirectly. Construction can assist the Three Gorge Project to relieve power shortages.